The Stages and Development of First Language Acquisition on Children 1,6 Years Old - Warni Warni; Rengki Afria; Julisah Izar; Maya Sari Harahap (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study describes the stages and development of children's first language using Indonesian. The object of this research is 2 children aged 1.6 years. The purpose of this study was to describe the stages and development of the first language in children. The method used is a qualitative method with a descriptive approach and the techniques used are observation and interviews. The data collected is documentation presented in tabular form. Data analysis using transcription, identification, and classification methods. The finding of this study is that CS is faster in language acquisition development at the phonological, morphological, and syntactic levels compared to MF. This is influenced by several factors such as gender, social, parenting, and environment.